Pneumonectomy in the treatment of tuberculosis relapse in a previously resected lung - D. B. Giller; A. A. Glotov; O. Sh. Kesaev; E. M. Glotov; Ya. G. Imagogev; V. V. Koroev; G. V. Shcherbakova; E. I. Khvalin (Вестник хирургии имени И.И. Грекова, 2020)
THE OBJECTIVE of our study was to increase the efficiency of treatment of tuberculosis postoperative reactivations in a previously operated lung, by clarifying the medical indications, improving surgical techniques and tactics when removing a previously resected lung.METHODS AND MATERIALS. We analyzed the results of treatment of 220 patients who, in the 2004–2017 timeframe in our institution, had pneumonectomies (76 cases) and pleuropneumonectomies (144 cases) for tuberculosis relapse in a previously operated lung. For more objective planning of surgical treatment and evaluation of its results, we identified three degrees of treatment radicalism: radical, conditionally radical, and palliative.RESULTS. 32 patients, who had carried a radical surgery, were diagnosed as having a complete clinical effect at the time of discharge (absence of destruction cavities in a single lung, bacterial excretion and illiquid complications) in 100 % of cases; in the group of patients operated conditionally radical, there were diagnosed 161 out of 168 (95.8 %) and in the group of patients operated palliative, there were distinguished only 3 cases out of 20 (15.0 %).CONCLUSION. The implementation of the completion pneumonectomy and pleurapneumonectomy is accompanied by high technical complexity and more frequent development of intraoperative and postoperative complications. At the same time, the high efficiency of treatment of tuberculosis relapses in a previously operated lung can be achieved using the recommended tactics and techniques of surgical treatment when performing radical and conditionally radical interventions.